PSMA5 contributes to progression of lung adenocarcinoma in association with the JAK/STAT pathway. (23rd May 2022) - Lu, Feng; Zhou, Jing; Chen, Qing; Zhu, Jianling; Zheng, Xiaowei; Fang, Na; Qiao, Ling
Abstract: Proteasome dysregulation is a common feature of cancer and a critical risk for tumorigenesis. However, the characteristics of proteasome components in tumor development and metastasis are poorly understood. PSMA5, an α5 subunit of the 20S core proteasome, is associated with the degradation of intracellular proteins. Increasing evidence indicated that it is involved in tumor development, but the underlying mechanism has remained unknown. Here, we show that PSMA5 is upregulated in lung adenocarcinoma (LUAD) cells and clinical LUAD tissues. Moreover, its upregulation is positively associated with lymph node metastasis and the poor prognosis of LUAD patients. PSMA5 knockdown inhibited the proliferation, invasion and metastasis of LUAD cells in vitro and in vivo, induced apoptosis of LUAD cells and sensitized LUAD cells to cisplatin. Furthermore, investigations revealed that PSMA5 overexpression inhibited cell apoptosis by activating the janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway in LUAD cells. In total, our results demonstrate that PSMA5 may function as a prognostic factor in LUAD. In addition, PSMA5 is a promising therapeutic target for LUAD, as its depletion induces cell apoptosis by inhibiting the JAK/STAT pathway. Graphical Abstract: